PEREMPUAN MENJADI IMAM SHALAT (Kajian Hukum dalam Perspektif Hadis) - M. Nasir Maidin (LPPM IAIN Parepare, 2016)
This paper examines the hadith related to the allowance of woman to be the priest in prayer where few men are her makmum. The scholars have different opinions about it; some scholars allowed, but other didn’t. Based on the writer’s analysis, the hadith which allowed woman to be the priest in prayer where few men are her makmum is categorized hadith daif. Hadith daif for the majority of scholars’ view cannot be used as hujjah in Islamic law.